2020
DOI: 10.1111/jcmm.15541
|View full text |Cite
|
Sign up to set email alerts
|

The ACE2 expression in Sertoli cells and germ cells may cause male reproductive disorder after SARS‐CoV‐2 infection

Abstract: The serious coronavirus disease‐2019 (COVID‐19) was first reported in December 2019 in Wuhan, China. COVID‐19 is an infectious disease caused by severe acute respiratory syndrome‐coronavirus 2 (SARS‐CoV‐2). Angiotensin converting enzyme 2(ACE2) is the cellular receptor for SARS‐CoV‐2. Considering the critical roles of testicular cells for the transmission of genetic information between generations, we analyzed single‐cell RNA‐sequencing (scRNA‐seq) data of adult human testis. The mRNA expression of ACE2 was ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
125
0
9

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(135 citation statements)
references
References 16 publications
1
125
0
9
Order By: Relevance
“…These infiltrated cells especially the lymphocytes and histiocytes, also damage the blood-testis barrier and destroy the seminiferous tubules directly( figure 5E,F). 41 Similar to other viruses like HIV, mumps and hepatitis B virus, SARS-CoV-2 also may lead to activation of inflammatory cytokines, which may potentiate the autoimmune response. They may cause orchitis by several mechanisms, which may result in the testicular damage leading to infertility and sterility, which may further increase the chances of testicular tumours.…”
Section: Histopathological Findings In Nervous Systemmentioning
confidence: 99%
“…These infiltrated cells especially the lymphocytes and histiocytes, also damage the blood-testis barrier and destroy the seminiferous tubules directly( figure 5E,F). 41 Similar to other viruses like HIV, mumps and hepatitis B virus, SARS-CoV-2 also may lead to activation of inflammatory cytokines, which may potentiate the autoimmune response. They may cause orchitis by several mechanisms, which may result in the testicular damage leading to infertility and sterility, which may further increase the chances of testicular tumours.…”
Section: Histopathological Findings In Nervous Systemmentioning
confidence: 99%
“…3). There is a lower expression of ACE2 in spermatocytes, late spermatocytes, spermatids and other somatic cells [82,83]. Furthermore, a high expression of the protease TMPRSS2 is also reported in germ and somatic cells.…”
Section: Angiotensin-converting Enzyme 2 In Male Reproductive Tissuesmentioning
confidence: 99%
“…Recently, a case report study showed that orchiepididymitis in a 14-year-old boy seemed to be a complication of COVID-19 (Gagliardi et al, 2020). Notably, higher expression of ACE2 in male gonads seems to be associated with younger age and, as a result, provides evidence that younger patients are more vulnerable to gonadal involvement by SARS-CoV-2 (Shen et al, 2020). Therefore, since the mechanism of involvement of different organs by SARS-CoV-2 is not fully understood, all the potential complications of the virus are based on assumptions and further research should be conducted to investigate the effect of SARS-CoV-2 on the male reproductive system and probable infertility.…”
mentioning
confidence: 99%